Reservoir Operation to Minimize Sedimentation - Dyah Ari Wulandari; Djoko Legono; Suseno Darsono (International Journal of Science and Engineering, 2014)
The Wonogiri Reservoir capacity decreases rapidly, caused by serious sedimentation problems. In 2007, JICA was proposed a sediment storage reservoir with a new spillway for the purpose of sediment flushing / sluicing from The Keduang River. Due to the change of reservoir storage and change of reservoir system, it requires a sustainable reservoir operation technique. This technique is aimed to minimize the deviation between the input and output of sediments. The main objective of this study is to explore the optimal Wonogiri reservoir operation by minimizing the sediment trap. The CSUDP incremental dynamic programming procedure is used for the model optimization.  This new operating rules will also simulate a five years operation period, to show the effect of the implemented techniques. The result of the study are the newly developed reservoir operation system has many advantages when compared to the actual operation system and the disadvantage of this developed system is that the use is mainly designed for a wet hydrologic year, since its performance for the water supply is lower than the actual reservoir operations.Doi: 10.12777/ijse.6.1.16-23 [How to cite this article:  Wulandari, D.A., Legono, D., and Darsono, S., 2014. Reservoir Operation to Minimize Sedimentation. International Journal of Science and Engineering, 5(2),61-65. Doi: 10.12777/ijse.6.1.16-23]